التخطيط الاستراتيجي وأثره على السياسة الخارجية - عبد الفاضلأ.محمد محمد (Aljameai)
المستخلص: إن التخطيط الاستراتيجي للسياسة الخارجية ذو اهمية وضرورة لتحقيق الأهداف، وهو عملية علمية أساسها التفكير وجمع المعلومات وتحليلها بتجرد وموضوعية، والتخطيط الاستراتيجي قابل للتحوير وفقاً لمعطيات وقدرات الدولة المتغيرة، فما كان ممكناً قد يأتي عليه وقت يكون غير ذلك لأسباب داخلية أو خارجية. التخطيط الاستراتيجي هو عملية تتسم بالإبداع، والقابلية للاختبار في أي مرحلة، ويتطلب التوافق بين من يخطط ويصمم الاستراتيجية ومن ينفذها. Abstract: Strategic planning for foreign policy is important and necessary to achieve goals .and its a scientific process its basis is thinking .collecting and analyzing information impartially and objectively .and strategic planning is subject to change according to Due to the changing data and capabilities of the state .what was possible may come at a time when it is otherwise for internal reasons or External. Strategic planning is a process that is creative .testable at any stage .and requires consensus between whom Plans and designs the strategy and implements it. Key Words: Planning ,The Strategy, Planning Strategic, Self Evaluation.